ARE EMPIRES RETURNING? - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2025)
In the processes of competition, to defend legitimate interests and protect the possibility of independent choice, working out of independent decisions, significant demographic, political, military, economic and other potential and the ability to realize it are required. The agenda is actively formed by the great powers. Does this circumstance mean the inevitability of the world entering a new period of unification and omnipotence of empires, a departure from the practice of realizing the rule “divide et impera”? Should the stated claims from Greenland and Canada to Mexico and the Panama Canal (as well as some other leading transport corridors and critical deposits) with the renaming of topographic features be treated as a program for further actions of the great powers? What is the probability of successful agreement between the great powers of our time on the contours of a new structure of world development and security? How to get your bonus for participating in the next ordering of chaos? [1-9]. Meanwhile, the ninth wave of the general Fronde (in comparison with which even the discontent of J. Mazarin on the part of practically all strata of the population seems insignificant) could become the crest of an almighty tsunami and threatens the most destructive catastrophes at the systemic level. Should the loss of identity be assessed as a kind of price for security or as a condition for preserving, improving self-worth and freedom of self-disclosure? The “large battalions” of the economy, united by the diversity of culture, ideology, language, and faith, are still decisive. But now they do not blur national traditional values, but are based on them “in corpore”. The basic, backbone ones are not obviously impersonal globalist structures with supranational officials serving them (for example, euro-bureaucrats), but powerful national states and forces protecting their legitimate interests.